The determinants of innovative capacity in the medical sector in Central Europe and across the European Union - Hegerty, Scott W.; Weresa, Marzenna (Technological and Economic Development of Economy, 2023)
The recent COVID-19 crisis, as well as the resulting international response, have demonstrated the importance of medical innovation in meeting current and future health challenges. Yet capacity for innovation differs from country to country, and policymakers are wise to find ways to increase each nation’s ability to generate new solutions. This study examines medical innovation, measured as patents per capita, for 27 EU countries from 2004 to 2018. Modelling innovation as a function of international and domestic macroeconomic variables, government and private-sector R&D, the rate of return to physical and human capital, and a measure of risk, a dynamic panel analysis finds that real-exchange-rate volatility reduces patent applications for some countries, particularly in Central and Eastern Europe. The response to the explanatory variables differs by countries’ overall innovation levels, with innovation in weaker innovators reduced by risk and increased by higher education levels. In stronger innovators, the internal rate of return most strongly drives innovation, suggesting that this process more closely resembles “traditional” investments.First published online 15 November 2022